Grammatical Error on EFL Students’ Argumentative Writings: A Case Study - Vony Purnama, I Gusti Agung; Putu Arsana, Anak Agung (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2023)
A study on error analysis is an important way to see the ability of the students in the foreign language learning process, particularly in writing. This is also very meaningful to enrich the method of teaching particularly teaching English as a foreign language. Therefore, this study aims to investigate the grammatical errors in the students’ argumentative writings and to find the most frequent errors made by the students. There were thirteen students of the International Program argumentative writings used as the data in this study. This study is very important because the students will do their final project in the English language. The data were analyzed based on the Surface Strategy Taxonomy which includes omission, addition, misformation, and misorder. The finding shows that all students made grammatical errors in their argumentative writing. The finding showed that there were 13 errors of misformation, 12 errors of omission, 7 errors of addition, and the last was 1 error of misorder. The most frequent error was the error of misformation. This finding is expected to be used as a reference for the teacher in planning the lesson to improve the understanding of the students in argumentative writing.